Peningkatan Ketrampilan Bebahasa Inggris Bagi Karyawan Hotel Fovere Bandara Semarang (The Improvement of English Language Skill for Fovere Hotel Semarang Airport Staff) - Novita Al Ihyak Dieni (J-LEE - Journal of Law, English, and Economics, 2019)
The community service activity entitled "Improving English Language Skills for Fovere Hotel Semarang Airport Staff". The target partners are economically productive communities, namely hotel staff. The hospitality industry currently faced with intense competition, a hotel must be able to have excellent service to win the hearts of consumers. Because only hotels that have superior service will be able to win the competition. Hotel as a service business supporting tourism activities, where its management is carried out by professionals and supported by employess who have competence/good skills in the hospitality sector. English language skills have become very important for hospitality staff to have. It is because, not only guests from within the country who come to the hotel, but also guests from abroad. The English language skills are needed in establishing the communication. In the training program for hotel staff, it used communicative learning. This is because, training is held in the afternoon after they worked. So, if the training program is not interested to them, it will make English training less successful. English language exercises are more focused on how hotel staff can communicate. And proven, hotel staff are more fluently in using English when they did competency tests.